Development of serial X‐ray fluorescence holography for radiation‐sensitive protein crystals. (20th January 2023) - Ang, Artoni Kevin R.; Umena, Yasufumi; Sato-Tomita, Ayana; Shibayama, Naoya; Happo, Naohisa; Marumi, Riho; Yamamoto, Yuta; Kimura, Koji; Kawamura, Naomi; Takano, Yu; Matsushita, Tomohiro; Sasaki, Yuji C.; et al.
Abstract : In this work, serial X‐ray fluorescence holography is developed and its capabilities are demonstrated by obtaining hologram patterns from the protein crystal Photosystem II before any signs of radiation‐induced damage. This new technique paves the way for future experiments on protein crystals that aim to clarify the local atomic structure of their functional metal clusters. Abstract : X‐ray fluorescence holography (XFH) is a powerful atomic resolution technique capable of directly imaging the local atomic structure around atoms of a target element within a material. Although it is theoretically possible to use XFH to study the local structures of metal clusters in large protein crystals, the experiment has proven difficult to perform, especially on radiation‐sensitive proteins. Here, the development of serial X‐ray fluorescence holography to allow the direct recording of hologram patterns before the onset of radiation damage is reported. By combining a 2D hybrid detector and the serial data collection used in serial protein crystallography, the X‐ray fluorescence hologram can be directly recorded in a fraction of the measurement time needed for conventional XFH measurements. This approach was demonstrated by obtaining the Mn K α hologram pattern from the protein crystal Photosystem II without any X‐ray‐induced reduction of the Mn clusters. Furthermore, a method to interpret the fluorescence patterns as real‐space projections of the atoms surrounding the Mn emitters has been developed, where the surrounding atoms produce large dark dips along the emitter–scatterer bond directions. This new technique paves the way for future experiments on protein crystals that aim to clarify the local atomic structures of their functional metal clusters, and for other related XFH experiments such as valence‐selective XFH or time‐resolved XFH.